A preliminary investigation of a novel method to manipulate penis length to measure female sexual satisfaction: a single‐case experimental design. (7th May 2021) - Veale, David; Vaidya, Aashay; Papageorgiou, Andriani; Foks, Melissa; Giona, Simone; Hodsoll, John; Freeston, Mark; Muir, Gordon
Abstract : Objectives: To investigate a novel methodology and explore whether artificially reducing the depth of penetration during intercourse matters to women. Study Design and Methods: A study with a single‐case experimental design (' n of 1'), in which a heterosexual couple act as their own control and the study is then replicated in subsequent couples, was conducted. Thirty‐five couples were assessed for eligibility to participate. Twenty‐nine couples without any sexual problems were randomized and 12 submitted sufficient data to analyse. As a proxy for reducing penis length, we artificially reduced the depth of penetration by using different sizes of silicone rings around the base of the man's erect penis. The main outcome measures were provided by the female partner on a scale of 0–100 and comprised: degree of (i) overall sexual pleasure; (ii) sexual pleasure from intercourse alone; and (iii) emotional connection to the male partner. The female partner was also asked before the experiment began to rate the degree of positive or negative change that would be personally meaningful for her. Results: On average, reducing the depth of penetration led to a statistically significant 18% reduction of overall sexual pleasure with an average 15% reduction in length of the penis. The longer the erect penis, the less likely the rings were to have an impact on sexual pleasure. There was a range of individual responses, however, with a minority of women reporting that reducing the depth of penetration was more pleasurable on some occasions. Conclusions: Size may matter in women in a healthy stable relationship when there is penile shortening. Because of the small number of couples and the inclusion of men with an apparently long penis, our results are preliminary, and we welcome replication in a larger sample with a more diverse range of penile lengths. Our results should not be misinterpreted as meaning that increasing penile length will increase sexual pleasure in women.